2020
DOI: 10.3892/mco.2020.2152
|View full text |Cite
|
Sign up to set email alerts
|

Transformation from adenocarcinoma to squamous cell carcinoma associated with long‑term administration of EGFR‑TKIs

Abstract: Although patients with non-small cell lung cancer exhibiting EGFR mutations generally respond to tyrosine kinase inhibitors (TKIs), the majority of patients acquire resistance ~1 year after treatment. EGFR T790M mutations, MET or HER2 amplifications and phenotypic transformations contribute to the mechanism of EGFR-TKI resistance. The transformation of small cell lung cancer frequently occurs, although few convert to squamous cell carcinoma associated with the administration of EGFR-TKIs. The current study rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Şehitogullari et al also reported that robot-assisted surgery requires a significantly shorter hospital stay than conventional endoscopic surgery [19]. Artificial pneumothorax is widely used in robot-assisted surgery [18][19][20]. The less invasive nature of robot-assisted surgery is attributed not only to the advantages of the surgical technique, but also to the suppressive effect of artificial pneumothorax, as revealed in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Şehitogullari et al also reported that robot-assisted surgery requires a significantly shorter hospital stay than conventional endoscopic surgery [19]. Artificial pneumothorax is widely used in robot-assisted surgery [18][19][20]. The less invasive nature of robot-assisted surgery is attributed not only to the advantages of the surgical technique, but also to the suppressive effect of artificial pneumothorax, as revealed in this study.…”
Section: Discussionsupporting
confidence: 54%
“…As shown in Table 2, [10–31] a total of 27 cases of SQ transformation in EGFR mutated lung adenocarcinoma after treatment with EGFR TKIs have been reported. The ages of these patients were 40 to 80 years (median age was 62 years), and 18 patients (66.7%) were female.…”
Section: Discussionmentioning
confidence: 99%